A new oral testosterone undecanoate therapy comes of age for the treatment of hypogonadal men. (June 2020) - Swerdloff, Ronald S.; Dudley, Robert E.
Background: A novel formulation of oral testosterone undecanoate (TU) was studied in a long- and short-term phase III trial to evaluate safety and efficacy. Methods: Hypogonadal men (age 18–65 years; two morning serum testosterone (T) <300 ng/dl with signs/symptoms) were recruited into a 365 day (trial I) or 105 day (trial II), randomized, multicenter trial. Patients were randomized 1:1 to oral TU ( n  = 161) or T-gel ( n  = 160) in trial I, and 3:1 to oral TU, twice daily (BID) JATENZO® ( n  = 166) or a topical T product [Axiron® ( n  = 56)] in trial II. Dose adjustments were based on average T concentrations ( C avg). Efficacy was assessed based on T levels, body composition and bone density. Safety was assessed by standard clinical measures. Results: Oral TU efficacy (% of patients with eugonadal T C avg) was 84% (serum C avg = 628 ± 343 ng/dl) and 87% (serum T equivalent C avg ≈ 489 ± 155 ng/dl) in trials I and II, respectively. Oral TU significantly ( p  <0.0001) improved all Psychosexual Daily Questionnaire parameters in trials I and II. In trial I, lean mass increased 3.2 ± 2.7 kg and fat decreased by 2.4 ± 3.6 kg (both p  <0.0001) and bone density improved in hip (+0.012 ± 0.0225 g/cm 2 ) and spine (+0.018 ± 0.0422 g/cm 2 ) after 365 days (both p  <0.0001). Oral TU-associated adverse effects were consistent with other T-replacement therapies but oral TU patients experienced a greater number of mild gastrointestinal adverse effects. Oral TU subjects in both studies exhibited an increase in mean systolic blood pressure of about 3–5 mmHg. Oral TU was not associated with liver toxicity nor did it cause an elevation in high-sensitivity C-reactive protein or lipoprotein-associated phospholipase A2 (cardiovascular safety biomarkers) after 365 days of therapy. Conclusion: A new oral TU formulation was safe and effective and represents a significant therapeutic advance for the treatment of appropriate hypogonadal men.